Pediatric heart failure with preserved ejection fraction, a review - Quennelle, Sophie; Bonnet, Damien (Frontiers in Pediatrics, 2023)
Diastolic dysfunction refers to a structural or functional abnormality of the left ventricle, resulting in impaired filling of the heart. Severe diastolic dysfunction can lead to congestive heart failure even when the left ventricle systolic function is normal. Heart failure with preserved ejection fraction (HFpEF) accounts for nearly half of the hospitalizations for acute heart failure in the adult population but the clinical recognition and understanding of HFpEF in children is poor. The condition is certainly much less frequent than in the adult population but the confirmatory diagnosis of diastolic dysfunction in children is also challenging. The underlying causes of HFpEF in children are diverse and differ from the main cause in adults. This review addresses the underlying causes and prognostic factors of HFpEF in children. We describe the pulmonary hypertension profiles associated with this cardiac condition. We discuss diagnosis difficulties in clinical practice, and we provide a simplified diagnostic algorithm for HFpEF in children.